STUDI EKOLOGI Apis cerana (HYMENOPTERA: APIDAE) PADA KEBUN CAMPUR DI DESA PAGAR PUDING KECAMATAN TEBO ULU KABUPATEN TEBO PROVINSI JAMBI - -, Irsad - (STKIP PGRI Sumbar, 2014)
Apis cerana is the one of insecta that gives a benefit for human. Exactly because it is able to product honey. The colony of bees include from the queen bees, male bees and worker bees. In the life of Apis cerana influenced by the area, due to that had been done the research about the study of acology Apis cerana (hymenoptera:apidae) at the mixed garden in the dasar puding village, Tebo Ulu distric, Tebo regency, Jambi province with the purpose is to know the kind of trees that is uses to nestle, the kind of plenty plant that is visited by the worker bees, and the condition of are physic. This research was conducted in the dasar Puding village, Tebo ulu distric, Tebo regency, Jambi province, by using descriptive survey method, in July-August 2014. From the result of the research, the diamtere rod that is occupied to nestle is about 43,94-79,28 cm, the number of cavities that could potentially to nestle is 2 until 5 cavities. The plants that was visited the worker bees Apis cerana (Hymenoptera: Apidae) the mixed garden in the dasar puding village, Tebo ulu distric, Tebo regency, Jambi province is 24 species and 16 familia, The familia that have the greatest species is Leguminoceae that is 3 species.